IoT-enabled dye-sensitized solar cells: an effective embedded tool for monitoring the outdoor device performance. Issue 59 (29th September 2020) - Khamrang, Themmila; Velusamy, Marappan; Ramesh, Mohan; Jhonsi, Mariadoss Asha; Jaccob, Madhavan; Ramasubramanian, Kanagachidambaresan; Kathiravan, Arunkumar
Abstract : Herein, we have developed a tool for monitoring the outdoor performance of dye-sensitized solar cells. Abstract : Herein, we have developed a tool for monitoring the outdoor performance of dye-sensitized solar cells. In this regard, a new dye consisting of an N -aryl-substituted imidazole with N -alkylated carbazole as the donor and cyanoacrylic acid as the acceptor has been designed. The overall power conversion efficiency of the designed dye reached ∼50%, with respect to that of the N719-based device (4%) under similar experimental conditions. Further, the device was interfaced with an IoT system, which measured the voltage and transmitted the device parameters to the user's mobile phone through a cloud channel. The developed IoT tool provides a resolution of 0.0315 mV and a round-trip delay time of <0.32 s for transmitting the information to the user's mobile phone.